PENGKAJIAN STATUS GIZI BERDASARKAN PERSEN LEMAK TUBUH DAN PEMBERIAN KONSELING INTERPRETASI HASIL PENGUKURAN PADA PKM DI MILAD UNIVERSITAS AISYAH PRINGSEWU - Mayesti Akhriani (Jurnal Pengabdian Kepada Masyarakat Ungu( ABDI KE UNGU), 2023)
Percent body fat is an indicator of nutritional status that describes the distribution and the total body fat in the body. Measurement of percent body fat and efforts to achieve optimal nutritional status that can reduce the risk of degenerative diseases. The aims of this community service activity is to increase the knowledge of Aisyah Pringsewu University Milad participants regarding the interpretation of the results of body fat percent measurements and nutritional counseling as an effort to achieve normal fat percent. This activity was conducted on the anniversary of Aisyah Pringsewu University for 6 days on June 19 – June 24 2023. The total number of respondents was 35 people by measuring percent body fat using BIA (Bioelectrical Impedance Analysis), then students and lecturers of the Nutrition Study Program provided explanations of interpretation of the results and nutritional counseling. From the measurement results, the results obtained were an average body fat percentage of all respondents of 22.83 ± 9.28 percent. For male respondents, 57% had a low body fat percentage, and only 7.1% of male respondents had a high category. Meanwhile, for female respondents, respondents who had normal and high fat percentage categories were 52.4% and 28.6%. Respondents were given nutritional counseling using leaflets regarding food intake, increased physical activity and a healthy lifestyle.